James H. Robb, Man as infinite spirit, The aquinas lecture, 1974, Marquette University Publications, Milwlakee, 1974, 8 + 58 pp - Argerami, Omar (1976)
Fil: Argerami, Omar. Universidad Nacional de La Plata; Argentina